What Explains Persistent Inflation Differentials Across Transition Economies? - Felix Hammermann; Mark Flanagan (Kiel Institute for the World Economy (IfW), 2007)
Panel estimates based on 19 transition economies suggests that some central banks may aim at comparatively high inflation rates mainly to make up for, and to perhaps exploit, lagging internal and external liberalization in their economies. Out-of-sample forecasts, based on expected developments in the underlying structure of these economies, and assuming no changes in institutions, suggest that incentives may be diminishing, but not to the point where inflation levels below 5 percent could credibly be announced as targets. Greater economic liberalization would help reduce incentives for higher inflation, and enhancements to central bank independence could help shield these central banks from pressures.
Keywords: P24; E58; 330; inflation; transition economies; panel data; Inflationsrate; Inflation; Übergangswirtschaft; Geldpolitik; Schätzung; Osteuropa